2017
DOI: 10.1016/j.envres.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Chronic arsenic exposure and risk of carotid artery disease: The Strong Heart Study

Abstract: Background Inorganic arsenic exposure from naturally contaminated groundwater is related to vascular disease. No prospective studies have evaluated the association between arsenic and carotid atherosclerosis at low-moderate levels. We examined the association of long-term, low-to-moderate inorganic arsenic exposure with carotid arterial disease. Methods American Indians, 45 to 74 years old, in Arizona, Oklahoma, and North and South Dakota had arsenic concentrations (sum of inorganic and methylated species, μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 38 publications
4
20
0
Order By: Relevance
“…We found the linear model better using AIC as the selection criteria depicting the associations of low-level As concentration and CVD outcomes. Such a conclusion has already been confirmed by several epidemiological and biological studies [36,53,61]. However, it has been illustrated that several mechanisms of As toxicity, ranging from the generation of oxidative stress, inhibition of DNA repair to modulation of signal transduction pathways and perturbation of DNA methylation patterns, are likely to give rise to nonlinear dose-response relationships, especially at low concentrations [98,99].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We found the linear model better using AIC as the selection criteria depicting the associations of low-level As concentration and CVD outcomes. Such a conclusion has already been confirmed by several epidemiological and biological studies [36,53,61]. However, it has been illustrated that several mechanisms of As toxicity, ranging from the generation of oxidative stress, inhibition of DNA repair to modulation of signal transduction pathways and perturbation of DNA methylation patterns, are likely to give rise to nonlinear dose-response relationships, especially at low concentrations [98,99].…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, as it is difficult to convert plasma As to water As, we excluded two studies which could only provide plasma As concentration to lower the bias of exposure assessment [50,51]. In addition, as there was only one study analysing each of soluble E-selectin, myeloperoxidase, plasminogen activator inhibitor-1 (PAI-1), soluble Intercellular Adhesion Molecule 1 (ICAM-1) and soluble Vascular cell adhesion protein 1 (VCAM-1) [18], carotid atherosclerosis indices (CAIs) [52], common carotid intima media thickness, plaque score and the presence of plaque in the common carotid [53], peripheral vascular disease [54,55] as well as some other CVD subtypes and clinic markers [21,27,[56][57][58][59][60][61], respectively, these variables have not been included in our dose-response meta-analysis. Moreover, due to the fact that significant differences could be found regarding concentrations of matrix-metalloproteases (MMPs) using plasma vs. serum [62], we further excluded two studies which analysed the plasma MMPs and serum MMPs respectively to avoid bias in outcome ascertainment [18,21] ( Figure S1).…”
Section: Data Sourcesmentioning
confidence: 99%
“…A high level of monomethylarsonic acid has been reported with a significantly high occurrence of ischemic stroke incidence [146]. The Strong Heart Study, and other cohort studies, have demonstrated that low-to-moderate exposure to inorganic arsenic is positively associated with high occurrence of plaques and an increase in the thickness of carotid intima-media [147,148]. In these studies, higher levels of arsenic metabolite monomethylarsonic acid have been observed with increased carotid intima-media thickness.…”
Section: Arsenic (As)mentioning
confidence: 84%
“…Chronic inflammation and secretion of growth factors, such as IL-8, can also establish microenvironments supportive of tumor development [54]. Epidemiological studies carried out in various countries demonstrate that arsenic significantly increases the risk of atherosclerosis [55,56]. Several mechanisms may contribute to the development of atherosclerosis, including general pro-inflammatory cytokine secretion [10], increased ROS production [8], enhanced monocyte adhesion to vascular endothelium [57] and reduced cholesterol efflux from macrophages [7].…”
Section: Contribution To Diseases Associated With Chronic Environmentmentioning
confidence: 99%